2014
DOI: 10.1016/j.jval.2014.08.2312
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Using Subcutaneous Trastuzumab

Abstract: A641and capecitabine monotherapy in terms of incidence of diarrhea, vomiting, stomatitis/mucositis. The hand-foot syndrome occurrred in less than 5% in case of tegafur. Tegafur (in monotherapy or in combination with calcium folinate) is less costly than capecitabine. The difference in costs in favor of tegafur monotherapy amounted to € 1,956.97 per 1 patient per 6 months or € 3,778.53 per year; of tegafur + calcium folinate -€ 2,168.12 and € 4,220.06 per 1 patient per 6 and 12 months, respectively. ConClusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[5] A time-and-motion study within the PrefHer study demonstrated a mean time saving of 55-57 min of patient chair time and 13-17 min of active healthcare professional time per session with H SC compared with H IV, [6] and several countries have reported estimated increased hospital capacity and/or costsavings with H SC. [7][8][9][10][11][12][13][14][15][16][17] These data support a transition to SC delivery.…”
Section: Introductionmentioning
confidence: 83%
“…[5] A time-and-motion study within the PrefHer study demonstrated a mean time saving of 55-57 min of patient chair time and 13-17 min of active healthcare professional time per session with H SC compared with H IV, [6] and several countries have reported estimated increased hospital capacity and/or costsavings with H SC. [7][8][9][10][11][12][13][14][15][16][17] These data support a transition to SC delivery.…”
Section: Introductionmentioning
confidence: 83%
“…Data from other countries have demonstrated that for SC formulation of trastuzumab, less time is required for drug preparation and administration; moreover, fewer consumables are used. [10][11][12][13] A costminimisation analysis (CMA) study in Greece demonstrated that the total cost of therapy per patient was 21 870 euros (€) when using the SC formulation of trastuzumab, whereas it was €23 118 when using the IV formation of trastuzumab. The investigators concluded that use of the SC formulation of trastuzumab would provide cost savings for the Greek healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…10 A study in Spain revealed similar findings: the use of the SC formulation of trastuzumab led to a 19.4 to 28.8% cost savings in the hospital. 11 Additionally, a time-and-motion study in New Zealand compared medical resource utilisation between the IV and SC formulations of trastuzumab in patients with HER2-positive breast cancer. The potential cost saving was NZ$96.94 per patient per cycle.…”
Section: Introductionmentioning
confidence: 99%